Analisys Mortality Rate of Tuberculosis Patients Seen From Age and Length of Treatment at RSUD Dr. M. Haulussy Ambon Using the K-Means Clustering Algorithm for the Rapidminer Application - Doms Upuy; Citra Fathia Palembang (Jurusan Informatika, 2022)
Tuberculosis (TB) is an infectious disease that causes major health problems in the world by the bacterium Mycobacterium tuberculosis. It spreads through the air when people with TB cough or sneeze. Maluku was in the 10th position with the most TB cases in Indonesia in 2016. Various programs and activities to control TB in Ambon City are carried out, from the process of finding cases, treating patients, health promotions to sputum examination. After that, an evaluation is carried out as an effort to prevent and control to measure the level of success and effectiveness of institutional programs in order to achieve organizational goals. To find out the development of TB cases in Maluku, especially the city of Ambon, the research conducted this time also used the k-means clustering algorithm for the rapidminer application to analyze the death rate of TB patients in terms of age and length of treatment at RSU Dr. M. Haulussy Ambon. The research conducted obtained that the highest number of patients who died were in cluster 1 with an age range of 36-55 years, then followed by the second position in cluster 0 with an age range of 6-33 years, and the last in cluster 2 with a total number of patients. died in the age range of 59-84 years. The length of stay of patients in the hospital varies from half a day to day 21 and is experienced by patients who recover as well as die. The highest patient mortality rate is in the productive age group, rarely does exercise and often engages in active activities and meets many people every day, smoking habits and lack of knowledge about health are the causes of more productive age groups suffering from TB